An investigation on how partnerships are used as a tool for effective local economic development retail projects: the case of Bara Mall - Mabuza, Noxolo Peacemaker (My University, 2010)
Partnerships are regarded as the answer to many economic growth and development problems facing state and local governments today. This research attempted to explore how partnerships are used as a tool for effective local economic development retail projects and was carried out among a group of participants who were involved in the Bara Mall project in Soweto. A research questionnaire was used as the main instrument of data collection. The collected data was analysed qualitatively using thematic formats. The findings of the study demonstrated that partnerships in townships are private sector driven with no consultation of the community stakeholders. Racial differences and the perceived notion of entitlement hinder effective partnerships outcomes in townships. This research concludes by arguing for good governance, accountability and transparency as crucial in leading to succssful retail projects